Application of chitosan in the control of fungal infections by dermatophytes - Lopes, Ana I. (2017)
Dermatophytes are a group of fungi that can invade keratinized tissues of humans and other animals and produce an infection called Dermatophytosis. As chitosan possesses antimicrobial activity, it can potentially be used to treat dermatophytic infections. The main objective of this work was therefore, to evaluate the antifungal activity of chitosan upon some dermatophytes, namely Microsporum canis and Trychophyton rubrum. In view of this, Minimum Inhibitory (MICs) and Minimum Fungicidal Concentrations (MFCs) of chitosans upon the fungi were determined. Moreover, in order to understand the effect of chitosan on fungal activity, hair was infected with these fungi in the presence and absence of chitosan and Scanning Electron Microscopy (SEM) images were obtained and analyzed. Lastly, keratin-azure was used as substrate to evaluate the effect of chitosan on keratin degradation by M. canis and T. rubrum. The results showed that chitosan possesses antifungal activity against T. rubrum and M. canis, presenting MICs and MFCs ranging from 1.1 to 2.2 mg/mL. The antifungal activity of chitosan is concentration dependent. The analysis of SEM images of hair infected with these dermatophytes revealed that chitosan seems to have a protective effect on the hair, reducing the extent of damage when compared to the control. Chitosan also displayed important activity in preventing proteases’ action and in preventing hair damage. Based on the obtained results, it’s possible to conclude that chitosan showed relevant antifungal activity against dermatophytes, which opens good prospects to the use of chitosan as an alternative for the conventional fungal treatments